Agricultural Indebtedness and Livelihood Diversification in Uttar Pradesh: A Study of the Eastern and Bundelkhand Regions. Issue 2 (December 2022) - Varkey, Shinu
The study aims to address the issue of indebtedness among agrarian households and the associated livelihood diversification using the cases of the Eastern and Bundelkhand regions of Uttar Pradesh. It raises the following broad questions: What is the nature and extent of the debt burden experienced by the farmer households of the study areas? How do these households diversify their livelihood strategies? And what explains the livelihood outcomes of these households? It is argued that the skewed distribution of productive resources in the study regions leads to various kinds of interlinked transactions among agrarian classes in the context of production and exchange. Such interlinkages are essentially exploitative, resulting in lower crop productivity and lower returns from cultivation. In the face of lower returns from cultivation, farmers are compelled to take recourse to borrowing. The majority of these borrowings, especially by the poorer classes, are from informal sources, exposing them to usurious extortions at the hands of money lenders, traders and rich peasants/farmers, leading to difficulties in meeting payment obligations and, finally, to indebtedness. The higher debt burden has resulted in an increased livelihood diversification by agrarian households in recent years, mostly to the informal sector. We term it forced livelihood diversification, because such diversification is not the natural outcome of a development process but is forced upon the peasantry because of the non-viability of cultivation.